2018
DOI: 10.1080/21645515.2018.1482171
|View full text |Cite
|
Sign up to set email alerts
|

The skin prick test response after allergen immunotherapy in different levels of tIgE children with mite sensitive Asthma/Rhinitis in South China

Abstract: The SPT grade change can be used for efficacy evaluation. Children with lower level of tIgE and higher ratio of sIgE/tIgE that obtain a more satisfactory effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The diagnosis of AR was carried out by our doctors following published procedures. 9 All AR patients had perennial AR history at least two years, DME skin prick test positive (the response at least 3 mm greater than the negative control 10 ), serum DME specific IgE positive (greater than 0.35 kU/l), did not use any anti-allergy therapies at least 2 weeks. The human subject demographic data are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of AR was carried out by our doctors following published procedures. 9 All AR patients had perennial AR history at least two years, DME skin prick test positive (the response at least 3 mm greater than the negative control 10 ), serum DME specific IgE positive (greater than 0.35 kU/l), did not use any anti-allergy therapies at least 2 weeks. The human subject demographic data are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…We adopted strict operational quality control in the SPT method. In addition to the allergen allergy itself, the accuracy of the SPT results is affected by many factors, including skin reactivity, age, [ 23 ] medication, [ 24 ] needle material, [ 25 ] and manipulation. [ 26 ] The purpose of the skin scratch test is to exclude false-positive results caused by a positive skin scratch sign.…”
Section: Discussionmentioning
confidence: 99%
“…This change is accompanied by induced blocking antibodies (particularly, of the subclass IgG4) [ 107 ]. The sIgE/tIgE ratio is often increased following AIT treatment [ 108 109 110 111 112 ], however, no changes are observed when evaluated less than 2 years of AIT treatment [ 113 ]. The blocking activity of IgG antibodies maintains unchanged for at least 2 years of discontinuation of AIT, despite the reduction in the IgG1 and IgG4 levels [ 114 ], suggesting long-term immune tolerance following cessation of AIT treatment.…”
Section: Predictive Biomarkers For Ait Outcomes In Allergic Diseasesmentioning
confidence: 99%
“…Changes in skin prick test (SPT) have a high degree of diagnostic performance in the evaluation of efficacy in HDM-SCIT according to tIgE levels [ 111 ]. Recently, one study reported the increased sensitivity and clinical relevance of the intradermal test compared to SPT to predict AIT effectiveness in respiratory allergic diseases [ 115 ].…”
Section: Predictive Biomarkers For Ait Outcomes In Allergic Diseasesmentioning
confidence: 99%